Survey of buffer management policies for delay tolerant networks. Issue 3 (31st March 2014) - Jain, Sweta; Chawla, Meenu
Abstract : Delay tolerant networks (DTN) are a class of networks that are a subset of the traditional mobile ad‐hoc networks. It differs from mobile ad hoc networks (MANETs) in the sense that it can withstand high delays in delivering data because of frequent network partitions, limited bandwidth and storage constraints persisting in such networks. Owing to these inherent characteristics of the delay tolerant networks improving delivery ratio in such networks depends on two main factors‐use of routing strategy and a good buffer management policy. Many routing protocols have been proposed in the literature for DTN. Buffer management is a very important factor in DTN because of the very limited buffer space available in DTN nodes. Although a scheduling policy in DTN determines which message has to be forwarded first, the dropping policy decides which messages are to be dropped in case of buffer overflow. This Letter presents a survey of the existing buffer management policies proposed for DTN and discusses the pros and cons of these approaches. The buffer management techniques have been classified on the basis of information used by them whether they are based on local information of messages available at the node or global information of all the messages in the network.